Uganda : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Uganda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
The Ugandan authorities reacted swiftly to the COVID-19 crisis, locking down the economy, saving lives and avoiding a public health crisis. However, the resulting economic and social costs have been high. Per capita GDP growth remains below pre-pandemic levels, poverty gains have been reversed, fiscal balances have deteriorated, and pressures on external buffers remain high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Uganda